Hardware implementation of transmitter for CDM based 2x2 MIMO channel sounder - Ullah, Mohammad Habib (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
This thesis is concerned with design and hardware implementation of transmitter for CDM (Code Division Multiplexing) based 2×2 MIMO (Multiple Input Multiple Output) channel sounder. MIMO wireless communication system is an innovative solution to improve the spectral efficiency by exploiting multipath-richness of the propagation environment. The degree of multipath-richness of the channel will determine the capacity gain attainable by MIMO deployment. Therefore, it is very important to have accurate knowledge of the propagation environment/radio channel before MIMO system is implemented. The radio channel behavior can be studied by channel measurement or channel sounding. CDM is one of the channel sounding techniques that allow accurate measurement at the cost of hardware complexity. CDM based channel sounder, requires code with excellent auto-correlation and crosscorrelation properties which generally difficult to be achieved simultaneously. Recently, loosely synchronous (LS) code has been proposed to meet the requirements. In this research, we design and implement the 2x2 MIMO transmitter to develop a CDM 2x2 MIMO channel sounder. However due to hardware limitation the implemented system has chip rate of 7.68 MCps, using LS code of length 8190 bits we can measure delay of not less than 0.13 μs and no more than 520 μs.